Hartman’s solution or normal saline in the treatment of hyperemesis gravidarum among South East Asian population: a randomised controlled trial” - I, Adibah; D, Khursiah; AI, Ahmad; NNM, Zaki (IIUM Medical Journal Malaysia, 2008)
Introduction: The aim of treatment for hyperemesis gravidarum is to stop vomiting, correction of dehydration, starvation and electrolytes imbalance. The common types of fluid used for fluid replacement are isotonic solutions like normal saline and hartman’s solutions. The absence of potassium in normal saline makes hartman’s solution superior but there is a possibility that the lactate component in hartman’s solution could worsen the starvation state of the patients. This study is to evaluate which of these two solutions is more effective for fluid replacement in hyperemesis gravidarum. The objectives are to compare which solution corrects dehydration, hypokalaemia and acetonuria faster and to evaluate whether the ketosis state is aggravated by lactate component in hartman’s solution. Materials and Methods: Patients with hyperemesis gravidarum were randomised to receive either Hartman;’s solution or normal saline at the rate of 125mls/ hour. Blood urea and serum electrolytes, haematocrit, lactate and urine acetone were taken during admission and repeated every 12 hours. The volume of fluid required to correct dehydration, hypokalaemia and acetonuria were compared. Comparison of the pre and post treatment level of serum lactate were also done. Results: Both hartman’s solution and normal saline are both effective in correcting dehydration (11.52±3.28 pints versus 11.94 ± 2.30pints respectively) and acetonuria (11.64 ± 2.75 pints versus 11.64 ± 2.54 pints respectively). A lower volume of hartman’s solution was needed to correct hypokalaemia (8.34 ± 2.44 pints versus 8.88 ± 2.63 pints) but was not statistically significant. Ketonaemia was not made worse after treatment with hartman’s solution. Conclusion: Normal saline and hartman’s solution are equally effective in treating complications of hyperemesis gravidarum.